Prompt Engineering and AI Agents with ChatGPT. - Villalobos, Ray (linkedin.com, 2024)
Engineering AI Agents improves how you complete longer tasks with ChatGPT, providing more accurate solutions that go beyond simple answers and move towards reusable workflows.